Liposome‐Encapsulated Hemoglobin Accelerates Skin Wound Healing in Diabetic dB/dB Mice. Issue 4 (21st March 2017) - Fukui, Tsuyoshi; Kawaguchi, Akira T.; Takekoshi, Susumu; Miyasaka, Muneo; Sumiyoshi, Hideaki; Tanaka, Rica
Abstract: Since liposome‐encapsulated hemoglobin with high O2 affinity ( h ‐LEH, P50 O2  = 10 mm Hg) has been reported to accelerate skin wound healing in normal mice, it was tested in dB/dB mice with retarded wound healing, as seen in human diabetics. Two full‐thickness dorsal wounds 6 mm in diameter encompassed by silicone stents were created in dB/dB mice. Two days later (day 2), the animals were randomly assigned to receive intravenous h ‐LEH (2 mL/kg, n  = 7) or saline (2 mL/kg, n  = 7). The same treatment was repeated 4 days after wounding (day 4), and the size of the skin lesions was analyzed by photography, surface perfusion was detected by Laser‐Doppler imager, and plasma cytokines and chemokines were determined on days 0, 2, 4, and 7, when all animals were euthanized for morphological studies. The size of the ulcer compared to the skin defect or silicone stent became significantly reduced on days 4 and 7 in mice treated with h ‐LEH (47 ± 8% of original size), similar to the level in wild‐type mice, compared to saline‐treated dB/dB mice (68 ± 18%, P  < 0.01). Mice treated with h ‐LEH had significantly attenuated inflammatory cytokines, increased surface perfusion, and increased Ki67 expression on day 7 in accordance with the ulcer size reduction, while there was no significant difference in chemokines, histological granulation, epithelial thickness, and granulocyte infiltration detected by immunohistochemical staining in the ulcer between the treatment groups. The results suggest that h ‐LEH (2 mL/kg) early after wounding may accelerate skin wound healing in dB/dB mice to levels equivalent to wild‐type mice probably via mechanism(s) involving reduced hypoxia, increased surface perfusion, suppressed inflammation, accelerated in situ cell proliferation and protein synthesis.